Clomiphene citrate prevents premature luteinization in stimulated intrauterine insemination cycles - Sultana, Nighat; Munmun, Sadia Afrin; Akhter, Dilruba; Yasmin, Mahamuda; Ishrat, Shakeela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Approximately 13-36% of ovarian stimulation and intrauterine insemination cycles are complicated by premature luteinizing hormone (LH) surge. Gonadotropin releasing hormone (GnRH) agonist or antagonist has been traditionally used to prevent a premature LH surge and premature luteinization in ovarian stimulation cycles. Clomiphene citrate, which competitively inhibits estrogen binding to estrogen receptors, may be used to prevent premature luteinization and premature LH surge in ovarian stimulation with gonadotropins prior to intrauterine insemination (IUI). The objective was to compare the effects of clomiphene citrate with placebo on prevention of premature luteinization in ovarian stimulation with intrauterine insemination cycles. Methods: This randomized controlled study was conducted from July 2021 to December 2022. A total of 76 participants had ovarian stimulation with tab letrozole and injection r-FSH. Transvaginal ultrasound for folliculometry was done from day 8 onwards as needed. When the leading follicle was at least 14 mm, women were randomly assigned to clomiphene citrate group (n=38) or placebo group (n=38). They were given clomiphene citrate 150 mg or placebo daily up to the day of trigger. Premature LH surge and premature luteinization were assessed on the day of trigger. Results: Premature luteinization was significantly lower in patients given clomiphene citrate compared to women given placebo (16.7% versus 47.1%, p<0.01). Premature LH surge was also lower in participants given clomiphene citrate but the difference was not statistically significant (47.2% versus 52.9%, p<0.811). Pregnancy rate with clomiphene citrate was higher (11.1% versus 2.9%) than that with placebo. Conclusions: The addition of clomiphene citrate to gonadotropins in mid to late follicular period decreases the risk of premature luteinization and improves pregnancy rate.